2013
DOI: 10.1002/ijc.28001
|View full text |Cite|
|
Sign up to set email alerts
|

Caveolin‐1 is a novel regulator of K‐RAS‐dependent migration in colon carcinogenesis

Abstract: Caveolin-1 is an essential component of membrane caveolae. It is an important regulator of cellular processes such as signal transduction and endocytosis. We report here, for the first time, that caveolin-1 is a target of the K-RAS oncogene in colon carcinogenesis. Caveolin-1 is induced in colon cancer cells and in human colon tumor samples, in response to K-RAS activating mutations. An activated K-RAS oncogene transcriptionally induces caveolin-1 expression in human colon cancer cells and this effect is not r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 60 publications
(114 reference statements)
5
33
0
Order By: Relevance
“…Together these findings are consistent with a model in which K-Ras activation drives the up-regulation of activated eIF5A, which in turn, promotes Rho/ROCK expression, leading to cytoskeletal reorganization as well as other pro-tumorigenic and pro-survival programs necessary for cancer metastasis. In support of this model, K-Ras has been shown to stimulate RhoA/ROCK signaling to promote tumor cell survival and metastasis (43)(44)(45)(46). However, K-Ras-induced eIF5A expression also likely contributes to tumor metastasis by modulating the expression levels of other key signaling/cytoskeletal proteins including PEAK1 (pseudopodium-enriched atypical kinase 1), which is critically involved in PDAC progression (13).…”
Section: Discussionmentioning
confidence: 97%
“…Together these findings are consistent with a model in which K-Ras activation drives the up-regulation of activated eIF5A, which in turn, promotes Rho/ROCK expression, leading to cytoskeletal reorganization as well as other pro-tumorigenic and pro-survival programs necessary for cancer metastasis. In support of this model, K-Ras has been shown to stimulate RhoA/ROCK signaling to promote tumor cell survival and metastasis (43)(44)(45)(46). However, K-Ras-induced eIF5A expression also likely contributes to tumor metastasis by modulating the expression levels of other key signaling/cytoskeletal proteins including PEAK1 (pseudopodium-enriched atypical kinase 1), which is critically involved in PDAC progression (13).…”
Section: Discussionmentioning
confidence: 97%
“…[25][26][27] Previous study showed let-7 is complementary to multiple sequences in the 3 0 UTR of human RAS genes, and represses its expression. 28 NF-kB can act as downstream of Ras pathway.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 These findings reveal an unexpected role for WT1 as a key regulator of the genetic network of oncogenic K-RAS and provide important insight into the mechanisms that regulate proliferation in response to oncogenic signals. [11][12][13][14] In the present study, molecular genetics analyses were not performed and this is a limitation of the study. Therefore we don't know the WT1 gene status of the patients.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies showed that Cav1 facilitate both ERK and AKT signaling in cancer cells from kidney, ovary, colon, prostate, epidermis, muscle, brain and is associated with promoting cell invasion, proliferation, angiogenesis and multi-drug resistance. [12][13][14][15][16][17][18][19][20] Most authors suggested that Cav-1 positive tumor cells served as tumor promoters by these signaling pathways. 3,[12][13][14][15][16][17][18][19] In the present study, we determined Cav-1 expression nearly in the half of tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation